Association of Inflammation and Endothelial Dysfunction with Coronary Microvascular Resistance in Patients with Cardiac Syndrome X - Long,Ming (2017)
Abstract Background: Although a proportion of CSX patients have impaired brachial artery flow-mediated dilatation (FMD) in response to hyperemia, suggesting that endothelial dysfunction in these patients may be systemic and not just confined to the coronary circulation; the underlying mechanisms triggering endothelial dysfunction in these patients are still incompletely understood. Objectives: To assess the association of the index of Microcirculatory Resistance (IMR) with endothelial dysfunction and inflammation in patients with CSX. Methods: We studied 20 CSX patients and 20 age and gender-matched control subjects. Thermodilution-derived coronary flow reserve (CFR) and IMR were measured using a pressure-temperature sensor-tipped guidewire. Brachial artery FMD was measured using high-resolution, two-dimensional ultrasound images obtained with a Doppler ultrasound device (HDI-ATL 5000, USA) with a 5 MHz to 12 MHz linear-array transducer. Results: Compared with in control subjects, CFR was significantly lower (2.42 ± 0.78 vs. 3.59 ± 0.79, p < 0.001); IMR was higher (32.2 ± 8.0 vs. 19.5 ± 5.5, p < 0.001); the concentration of hs-CRP and FMD was higher (4.75 ± 1.62 vs. 2.75 ± 1.50; 5.24 ± 2.41 vs. 8.57 ± 2.46, p < 0.001) in CSX patients. The Duke treadmill score (DTS) was correlated positively to CFR and FMD (0.489 and 0.661, p < 0.001), it was negative to IMR and hsCRP (-0.761 and -0.087, p < 0.001) in CSX patients. Conclusions: The main finding in this study is that the DTS measured in patients with CSX was associated to hsCRP and FMD. Moreover, the independent effects of exercise tolerance can significantly impair FMD and hsCRP in CSX patients; especially it is particularly important to whom where FMD was associated negatively with IMR.